2019
DOI: 10.1167/iovs.19-27493
|View full text |Cite
|
Sign up to set email alerts
|

Chitinase-3-Like-1 Promotes M2 Macrophage Differentiation and Induces Choroidal Neovascularization in Neovascular Age-Related Macular Degeneration

Abstract: Chitinase-3-like-1 promotes M2 macrophage differentiation and induces choroidal neovascularization in neovascular age-related macular degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 46 publications
3
60
2
Order By: Relevance
“…Other studies have reported that CHI3L1 contributes to polarization to M2 macrophage [48][49][50], but in our results, K284-6111-administrated Tg2576 mouse showed lower mRNA level of Tnf, Il1b, Il6, and Cd86. Moreover, overexpression of CHI3L1 increased the expression of markers of M1 microglia, Tnf, Il1b, Il6, and Cd86, and inhibited by K284-6111 treatment.…”
Section: Discussioncontrasting
confidence: 94%
“…Other studies have reported that CHI3L1 contributes to polarization to M2 macrophage [48][49][50], but in our results, K284-6111-administrated Tg2576 mouse showed lower mRNA level of Tnf, Il1b, Il6, and Cd86. Moreover, overexpression of CHI3L1 increased the expression of markers of M1 microglia, Tnf, Il1b, Il6, and Cd86, and inhibited by K284-6111 treatment.…”
Section: Discussioncontrasting
confidence: 94%
“…Consistent with our previous findings, the present study showed that overexpression of CHI3L1 increased expression of pro-inflammatory cytokines, Cd86 , one of the markers of M1 microglia, and inflammatory proteins in CHI3L1 overexpressing BV-2 cells. Other studies have reported that CHI3L1 contributes to polarization to M2 macrophage [ 50 52 ], but in our results, K284-6111-administrated Tg2576 mouse showed lower mRNA level of Tnf, Il1b, Il6, and Cd86 . Moreover, overexpression of CHI3L1 increased the expression of markers of M1 microglia, Tnf, Il1b, Il6, and Cd86 , and inhibited by K284-6111 treatment.…”
Section: Discussioncontrasting
confidence: 91%
“… 143 Upon recruitment and activation, CHI3L1 induces M2 macrophage (alternatively activated) differentiation by the phosphorylation of Erk. 19 , 148 Conversely, CHI3L1 is highly expressed in S. aureus -stimulated macrophages, where it promotes M1 polarization of macrophages (classically activated) via activation of the MAPK pathway. 149 Mechanistically, CHI3L1 secreted from M2 macrophages interacts with IL-13Rα2 on the plasma membrane of cancer cells, triggering the activation of the MAPK signaling pathway in GC and breast cancer.…”
Section: Chi3l1 In Oncogenesismentioning
confidence: 99%
“…CHI3L1 plays a crucial role in protecting against pathogens, antigen-induced and oxidant-induced injury responses, inflammation, and tissue repair and remodeling by regulating a variety of essential biological processes including oxidant injury, apoptosis, pyroptosis, inflammasome activation, Th1/Th2 inflammatory balance, M2 macrophage differentiation, dendritic cell (DC) accumulation, TGF-β1 expression, ECM regulation, and parenchymal scarring. 16 19 …”
Section: Introductionmentioning
confidence: 99%